The Teaching of Sociolinguistics to Students of the English Language Education Study Program at State Islamic University of Mataram - Pauzan (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
This study aims to explore the teaching of sociolinguistics to students of the English Language Education Study Program at the State Islamic University of Mataram through a comprehensive library research approach. The study was conducted within the context of higher education and focused on literature published primarily between 2022 and 2025. The population of this study consists of scholarly works related to sociolinguistics and language education, with a sample of 15 selected academic sources including peer-reviewed journal articles, books, conference proceedings, and institutional documents. The research instruments involved documentation techniques through systematic literature review and data extraction from relevant academic publications. The data were analyzed using a qualitative descriptive approach through thematic synthesis, which involved identifying patterns, themes, and conceptual frameworks related to sociolinguistic instruction. The findings indicate that sociolinguistics plays a significant role in English language education by enhancing students’ linguistic awareness, intercultural competence, and critical understanding of language ideology. In addition, effective pedagogical approaches such as contextual learning, project-based learning, and discussion-based learning enable students to connect theoretical knowledge with real-life language use. However, several challenges were identified, including limited instructional materials, lack of contextualization in local sociocultural settings, and the need for more interactive teaching strategies. Therefore, sociolinguistics instruction should emphasize contextual and student-centered learning to improve its effectiveness in teacher education programs.